2021
DOI: 10.1111/apce.12319
|View full text |Cite
|
Sign up to set email alerts
|

The impact of indirect tax on income distribution and poverty in Tanzania

Abstract: This paper analyzes the impacts of indirect tax benefits policy reforms on income distribution and poverty in Tanzania by applying a standard static microsimulation model TAZMOD v1.8. The simulations model two indirect tax reforms involving changes to the excise duty and value-added tax rates on alcoholic beverages and tobacco products, and changes to employers' and employees' contributions to the National Health Insurance Fund. The results of the first reform find a positive effect on government tax revenue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the same vein, Gupta and Jalles (2020) opined that tax revenues lead to a better distribution of income. Mmaskaeva et al (2021), reviewed the effects of indirect tax revenues on income distribution and poverty and concluded that during the first reform, indirect tax revenues have a neutral effect on income distribution and poverty. Nevertheless, under the second reform, indirect tax revenues have a positive effect on income distribution and poverty.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…In the same vein, Gupta and Jalles (2020) opined that tax revenues lead to a better distribution of income. Mmaskaeva et al (2021), reviewed the effects of indirect tax revenues on income distribution and poverty and concluded that during the first reform, indirect tax revenues have a neutral effect on income distribution and poverty. Nevertheless, under the second reform, indirect tax revenues have a positive effect on income distribution and poverty.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Overall, considering the gendered impact of consumption taxes is not straightforward. It requires an understanding of the overall progressivity of the tax and redistributive system, and a recognition that such taxes are often an important source of revenue for governments (Maskaeva et al 2021). Accordingly, analyses need to consider not just the stand-alone burden of indirect taxes, but also their contribution to government spending and social protection transfers, which in turn may promote gender equality (see, e.g., Ambel et al 2022).…”
mentioning
confidence: 99%